Aluminium scrap melting under different liquid aluminium flow conditions: part-II: two phase flow. (2nd July 2016) - Argyropoulos, S. A.; Li, Z.; Bussmann, M.; Doutre, D.; Sukhram, M.
Abstract : This experimental research work deals with aluminium (Al) alloy melting in an Al bath. In this liquid metal, nitrogen gas was introduced at specific locations and at different gas flow rates. The samples employed, along with their position in the liquid Al, and the procedure for melting detection, were identical with the ones utilised in Part I. The introduction of gas into liquid Al has different effects on the melting time of the immersed Al 6061 alloy cylinder. For the range of gas flow rates examined, the addition of gas into a stagnant Al bath (i.e. natural convection conditions) produces insignificant changes in melting time. However, when the liquid Al is moving (i.e. forced convection conditions), the gas addition leads to a sizeable reduction in melting time. The melting time reduction ratio is introduced as a way to compare the melting under single and two phase flow liquid Al conditions. It is found that this ratio is affected by the nozzle position and also by the gas flow rate. The concept of an equivalent single phase velocity is also introduced, and defines the single phase velocity of liquid Al which results in the same melting time of the cylinder as under two phase flow conditions. It is found that the equivalent single phase velocity is influenced by both the gas flow rate and the nozzle position. The parameter which most likely contributes to the acceleration of the melting rate in two phase flow is the turbulence intensity, which is expected to increase due to the nitrogen gas injection.